2016
DOI: 10.1155/2016/5269815
|View full text |Cite
|
Sign up to set email alerts
|

The Role Descriptions of Triage Nurse in Emergency Department: A Delphi Study

Abstract: Background. Triage nurses play a pivotal role in the emergency department. However some researchers have attempted to expand triage nurse's role; remarkable discrepancies exist among scholarly communities. The aim was to develop a role description of triage nurse relying on the experts. Methods. A modified Delphi study consisting of 3 rounds was performed from March to October 2014. In the first round, an extensive review of the literature was conducted. Expert selection was conducted through a purposeful samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Part one consisted of 15 items measuring nurses' knowledge in Managing Patients with Psychological Distress at EDs (MPSD) (item 1-15) using a visual analogue scale with responses ranging from 0 (not confident at all) to 10 (very confident). Part two, items 16 -30, was designated to measure knowledge regarding the physical and psychological Signs and Symptoms of Psychological Distress (SSPSD), where nurses asked to respond by yes (1), no (2), or do not know (3). The possible range of scores was 15-45.…”
Section: Nurses' Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Part one consisted of 15 items measuring nurses' knowledge in Managing Patients with Psychological Distress at EDs (MPSD) (item 1-15) using a visual analogue scale with responses ranging from 0 (not confident at all) to 10 (very confident). Part two, items 16 -30, was designated to measure knowledge regarding the physical and psychological Signs and Symptoms of Psychological Distress (SSPSD), where nurses asked to respond by yes (1), no (2), or do not know (3). The possible range of scores was 15-45.…”
Section: Nurses' Knowledgementioning
confidence: 99%
“…The Emergency Department (ED) is a dynamic environment that challenges nurses to manage critical situations such as patients with psychological distress [1]. Nurses at EDs are confronted with patients complaining of physical signs connected to psychological distress which may influence the abilities of nurses to make an appropriate diagnosis and man-agement [2].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 On the whole, the results of the current study confirmed those of similar studies conducted in other parts of the world. 16,17 18,19 Although these measures may help reduce patient wait times, it often results in unnecessary tests being ordered. 11,20,21 For economic reasons, it is prudent to limit such requests for unnecessary tests, in turn reducing unnecessary hospital stays and admissions.…”
Section: Discussionmentioning
confidence: 99%
“…A modified Delphi study with 2 phases as described before was performed [1416]. This study was approved by the Shanghai Public Health Clinical Center Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Delphi, an approach to achieve a unified opinion through a number of rounds of consultation with experts' advice and feedback on a subject or matter, is widely employed by nursing research [1416]. Therefore, Delphi method is adopted in this study to fulfill our needs.…”
Section: Introductionmentioning
confidence: 99%